(untitled) (Global Journal of Human-Social Science, 2012)
This systematic study examines the survey of models was made to study Communication as the necessity of life. And if communication is oxygen for an individual and blood for society then channels of communication, work as nerves of the society. First of all, we would discuss ’Mass Communication and then ’Public Opinion’. We have tried to cover different aspects related to the topic. Both the portions are interdependent. Sources of Mass Communication are the most important means of framing public opinion, and media contents are in accordance of public opinion. As far as basic structure of mass media as concerned, it is adopted from western countries. So when we try to impose that theoretical pattern on our sociopolitical-economic set up, we find ourselves uncomfortable and incompatible. Indian writers are working in this field but still it is in western shades.